The Causes of Awaiting Trial of Inmates in Nigerian Correctional Service: A Case Study of Jos Correctional Center - Uwais, Idrees Abdullahi; Sulaiman, Usman Muhammad; Gwani, Abdullatif Isa (International Journal of Humanities, Education, and Social Sciences, 2025)
This study investigates the persistent issue of awaiting trial within the Nigerian correctional system, focusing specifically on inmates in Jos Correctional Service. The research aims to define the nature of the awaiting trial phenomenon, assess investigative failures, identify contributing factors, examine its socio-legal effects, and propose viable solutions. A total of 100 respondents were selected from five operational units in the Jos Correctional Service, comprising 80 awaiting trial inmates, 5 prison officials, 5 representatives of the High Court, and 10 officers from the Nigeria Police Force. Data collection employed structured questionnaires and interviews, with quantitative data analyzed using frequency distribution tables and qualitative data interpreted descriptively. Relevant literature was reviewed from academic journals, legal commentaries, newspapers, and magazines. The findings reveal that the prolonged detention of suspects without trial undermines the constitutional presumption of innocence and contributes to prison congestion, psychological distress, and systemic inefficiencies. Key factors identified include investigative delays, inadequate prosecutorial resources, and bureaucratic inertia within the judicial process. The study recommends the modernization of criminal investigations through the training of police personnel in contemporary techniques, the digitalization of court proceedings to expedite case handling, and the introduction of modern correctional models, such as privately managed facilities—albeit with cautious consideration of legal and ethical implications. The study concludes that awaiting trial is a pressing socio-legal issue that demands urgent reform and further empirical investigation to inform policy and institutional responses within Nigeria’s justice administration framework.